Teacher’s Use of Power Bases as Perceived by ELT Students in Tertiary Education - Bahar Bahar; Oikurema Purwati; Slamet Setiawan (Budapest International Research and Critics University, 2020)
This study attempts to examine Power relations perceived by students in classroom interaction in tertiary education Context. Good classroom interaction is perceived as one when all the students are actively engaged with what is happening in the classroom. This means that students are accounted for to be responsible for their own learning. A mixed-method was carried out by exerting questionnaires and focused interviews. The perception questionnaires were given to 40 students majoring in English Literature at Fajar University of Makassar on the Students’ perception toward power in the classroom context. In order to have more elaborated information about power relations in the classroom context, the researcher employed focused interviews with 10 students who were chosen randomly. The findings suggest that there are several things influenced power and solidarity in EFL classroom interaction, the majority of the students perceived that their teacher is a dominant figure in the classroom. Nonetheless, the students do recognize that when teachers are being dominant; it means they want everyone to equally participate in the class. Students also affirm that confidence is needed to be able to participate in classroom activities and that support from their classmates is influential to some extent.